Packaging method of liquid metal microspheres

By using hydrogel powder to coat liquid metal microspheres, the problems of uneven packaging and poor mechanical properties in the prior art are solved, and stable packaging and good biocompatibility of liquid metal microspheres are achieved, and suitable for a variety of application fields.

CN119819211AActive Publication Date: 2025-04-15ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311318775.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively encapsulate high-flowability liquid metal microspheres, resulting in uneven encapsulation shells and poor mechanical properties, making it difficult to meet the application needs in the fields of medical care and electronic information.

Method used

Hydrogel powder is used to coat liquid metal microspheres, and a hydrogel film is prepared by mechanical stirring and ultraviolet curing, controlling the shell thickness and inner core size to ensure the uniformity and adhesion of the hydrogel.

Benefits of technology

The stable packaging of liquid metal microspheres has been achieved, and a hydrogel shell with good biocompatibility and uniformity has been obtained. It is suitable for thermal management, interventional medical care and soft robots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819211A_ABST
    Figure CN119819211A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of liquid metal packaging, and relates to a method for packaging liquid metal microspheres, which comprises the following steps of: preparing hydrogel powder with self-gelation property and adhesion, preparing cured spherical liquid metal, and packaging the spherical liquid metal. The method for preparing the liquid metal coating is simple and universal, the obtained coating has good uniformity, and compared with an existing dip coating process, the method can avoid bottom accumulation of high-fluidity polymer liquid under the gravity effect in the curing process, so that the surface hydrogel coating has better uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of liquid metal packaging, in particular to a method for packaging liquid metal microspheres. Background Art

[0002] As an emerging material that can meet major national needs such as aerospace, medical health, and electronic information, liquid metal (gallium-based or bismuth-based) has attracted widespread attention due to its low melting point, excellent electrical conductivity, thermal conductivity, fluidity, low toxicity, and close to zero saturated vapor pressure.

[0003] In particular, in the medical field, liquid metals, which are naturally high in density, can act as new contrast agents in medical imaging examinations such as CT, MRI, and photoacoustic imaging to achieve efficient diagnosis and treatment. In addition, liquid metals can also generate heat under the action of external light, magnetic fields, or electric fields to achieve thermal ablation of tumors. At the same time, after liquid metals are dispersed into micro-nanoparticles, they can be modified with anticancer drugs to achieve synergistic treatments including chemotherapy. Flexible or rigid-flexible medical implantable electrodes or wearable devices based on liquid metals as physiological signal sensors have also become popular due to the active fields of brain-computer interfaces and flexible electronics.

[0004] However, due to the presence of sticky surface oxides (gallium oxide and indium oxide, etc.) and high reactivity, liquid metals will adhere to or wet on substrates including skin, glass and metal plates, making these liquid metals difficult to handle. In particular, liquid metals that enter the body by injection or swallowing often have frictional contact with the surrounding environment, so that the liquid metal will inevitably remain on the surface of the tissue passing through. This will undoubtedly bring great trouble to the subsequent recovery of liquid metals. Although liquid metals are considered to be non-cytotoxic, the role of liquid metals remaining in the body in the metabolic process is still unclear, that is, there are still certain safety risks. In addition, the presence of metal foreign matter in the body will also have a certain degree of impact on daily life, such as unnecessary troubles during security inspections. Therefore, it is necessary to appropriately and effectively encapsulate and protect liquid metals to reduce the problem of liquid metal leakage.

[0005] Currently encapsulating macro blocks (volume greater than 1mm 3) The liquid metal solution is mainly to inject or wet the liquid metal into a mold and then encapsulate it with a polymer material (such as silicone) [Adv. Sci. 2022, 2105289, Polymers 2021, 13, 2407]. In addition, the block can be broken into micron-sized particles by ultrasound or mechanical stirring, and then encapsulated by polymer materials for use in flexible electronics and other fields [Nature Communications (2019) 10: 1300]. However, these solutions all have problems such as complex preparation process, poor permeability of polymer materials such as silicone, too thick encapsulation shell and high cost.

[0006] As a material with high biocompatibility and similar mechanical properties to human tissue, hydrogel has been widely used in the biomedical field to reduce chemical stimulation and mechanical damage of implanted devices or wearable devices under long-term use. Compared with materials such as silica gel (such as polydimethylsiloxane PDMS), the hydrogel-coated material system has better permeability (including ions and aqueous solutions, etc.), so as to achieve a certain degree of interaction with the external environment. Therefore, the use of hydrogel to wrap bulk liquid metal has a wider application prospect. At present, some people have used objects to be soaked in hydrogel prepolymer to achieve the coating of hydrogel thin layer [Adv.Mater.2019,31,1807101, Adv.Mater.2019,1903062]. However, due to the weak mechanical properties of the hydrogel film obtained after dipping in the hydrogel prepolymer and the uneven shell layer caused by its surface sedimentation after a large amount of dipping in hydrogel. In addition, some people have used hydrogel to coat liquid metal micro-nanoparticles, but this solution is difficult to hold high-density metal blocks on macroscopic bulk liquid metal due to poor mechanical properties [Adv. Funct. Mater. 2018, 28, 1804197]. Therefore, it is still difficult to coat the surface of a macroscopic bulk liquid metal with high fluidity with a hydrogel shell layer of stable physical and chemical properties and relatively uniform controllable thickness. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for encapsulating liquid metal microspheres so as to more conveniently and quickly prepare a new type of liquid metal hydrogel capsule with excellent mechanical properties to ensure that the liquid metal does not leak easily during daily use or medical applications.

[0008] The technical solution adopted by the present invention to solve the technical problem is:

[0009] The first aspect of the present invention provides a method for encapsulating liquid metal microspheres, comprising the following steps:

[0010] Step 1, preparing a hydrogel powder with self-gelling properties and adhesion: mixing a polymerizable small molecule monomer A with a carboxyl group or a hydroxyl group, a polymerizable small molecule monomer B with a silanol group, a crosslinking agent, a photoinitiator, and deionized water in a volume ratio of 40-180:0.1-1:1-3:0.05-0.1:60-200, mechanically stirring and mixing, removing bubbles, and UV curing at room temperature for 3-5 hours; dialysis to remove unpolymerized small molecules in the hydrogel; crushing, freeze drying, and sieving to obtain a hydrogel powder with a particle size of 100 mesh to 400 mesh;

[0011] Prepare solidified spherical liquid metal, first shape the liquid metal into a sphere with a particle size of 1 mm to 3 cm through a mold, and then solidify it at a temperature of 10°C to -30°C;

[0012] Step 2: Encapsulate spherical liquid metal: control the ambient humidity below 40% and the temperature below the melting point of the liquid metal, spray the atomized glycerol aqueous solution on the liquid metal balls and put them into a container covered with hydrogel powder, shake the container to allow the metal balls inside to roll, and take out the liquid metal balls after the powder completely covers the liquid metal balls. Then put them into a new plastic container and continue rolling to remove the pseudo-adherent dry powder on the surface; finally, spray a small amount of glycerol aqueous solution to cover the surface of the metal balls to promote the re-dissolution of the gel dry powder attached to the surface to form a complete hydrogel film.

[0013] Furthermore, the polymerizable small molecule monomer A having a carboxyl group or a hydroxyl group is one or more of acrylic acid, 2-butenoic acid, and polyvinyl alcohol.

[0014] Furthermore, the polymerizable small molecule monomer B with silanol groups is one or both of [3-(methacryloyloxy)propyl]trimethoxysilane and vinyltrimethylsilane.

[0015] Furthermore, the cross-linking agent is one or both of N,N-methylenebisacrylamide and polyethylene glycol dimethacrylate.

[0016] Furthermore, the photoinitiator is one or more of benzophenone, α-ketoglutaric acid, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0017] Further preferably, the volume ratio of the polymerizable small molecule monomer A with carboxyl or hydroxyl group, the polymerizable small molecule monomer B with silanol group, the crosslinking agent, the photoinitiator, and deionized water is 60-100: 0.1-0.2: 1-3: 0.05-0.1: 150-200.

[0018] Furthermore, the liquid metal is a gallium-based or bismuth-based metal or alloy.

[0019] Furthermore, the volume percentage of the glycerol aqueous solution is 10 vol% to 50 vol%.

[0020] Furthermore, the dialyzed hydrogel is placed in liquid nitrogen. When the liquid nitrogen is no longer boiling, it is taken out of the liquid nitrogen and placed in a stirring crusher for crushing to obtain white hydrogel powder. The powder is then placed in a freeze dryer and freeze-dried at minus 70°C, preferably at -70°C to -120°C.

[0021] The second aspect of the present invention provides a liquid metal hydrogel capsule obtained by the above encapsulation method.

[0022] The third aspect of the present invention provides applications of the liquid metal hydrogel capsule in the fields of thermal management, interventional medicine, and soft robotics.

[0023] The advantages and positive effects of the present invention are:

[0024] 1. Compared with the currently commonly used polymethyl methacrylate and polydimethylsiloxane, the hydrogel thin layer used in the present invention has natural ion, small molecule and solvent permeability.

[0025] 2. The novel liquid metal hydrogel capsule of the present invention can controllably adjust the shell thickness and the inner core size by changing the number of rolling coating and the spherical mold to adapt to different size environments, for example, it can be adjusted to a suitable swallowing size for the human body.

[0026] 3. The gel dry powder used in the present invention is a three-dimensional network formed by copolymerization and cross-linking of acrylic acid molecules obtained by long-term dialysis and freeze-drying and a small amount of [3-(methacryloyloxy)propyl]trimethoxysilane as monomers, and has good biocompatibility. The polymerized high molecular weight polyacrylic acid has a large number of carboxyl groups, which can achieve healing between powders under the action of water re-dissolution and hydrogen bonding; and a small amount of [3-(methacryloyloxy)propyl]trimethoxysilane can not only provide Si-O-Si covalent cross-linking to improve the mechanical strength and stability of the re-dissolved hydrogel film, but also can produce a cross-linking reaction with the metal surface with hydroxyl groups to improve the adhesion to the metal. Here, acrylic acid can be replaced by various polymerizable small molecule monomers with carboxyl groups or hydroxyl groups, such as 2-butenoic acid or polyvinyl alcohol, and [3-(methacryloyloxy)propyl]trimethoxysilane can also be replaced by other polymerizable small molecule monomers with silanol groups, such as vinyltrimethylsilane.

[0027] 4. The method for preparing liquid metal coating of the present invention is simple and universal and the obtained coating has good uniformity. Compared with the previous dipping process, it can avoid the bottom accumulation of high-fluidity polymer liquid under the action of gravity during the curing process, thereby allowing the surface hydrogel coating to have better uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A flow chart is prepared for the method of the present invention;

[0029] Figure 2 This is a photo of the morphology of liquid metal hydrogel capsules during the preparation process;

[0030] Figure 3 is the amount of powder on the surface of the liquid metal hydrogel capsule and the coating thickness under different rolling times, wherein a) is the amount of powder on the surface of the liquid metal sphere under different rolling times; b) is the shell thickness on the surface of the liquid metal sphere under different rolling times;

[0031] Figure 4 is the compression performance of liquid metal hydrogel capsules with different shell thicknesses;

[0032] Figure 5 This is a photo of the liquid metal hydrogel capsule prepared in Example 2;

[0033] Figure 6 This is a photo of the liquid metal hydrogel capsule prepared in Example 3;

[0034] Figure 7 The liquid metal spheres are obtained by the drop dipping method and dipped in the hydrogel prepolymer solution;

[0035] Figure 8 After the liquid metal melts, the hydrogel cannot achieve long-term stable wrapping of the liquid metal with high deformation ability;

[0036] Fig. 9 It is pAAc powder after soaking in water;

[0037] Fig.10 The preparation process photos of Comparative Example 3, wherein A is a powder obtained by copolymerization with NIPAM instead of TMSPMA and coated on a solidified liquid metal ball; B is a hydrogel film and a liquid metal ball separated by being easily torn off with the help of tweezers; C is a hydrogel film and a liquid metal ball separated after losing mechanical properties after being soaked in water;

[0038] Fig.11 These are photos of the preparation process of Comparative Example 4, where A is the p(AAm-co-TMSPMA) hydrogel powder after immersion in water; and B is the hydrogel layer stretched and adhered to the surface of the solidified liquid metal sphere. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0040] Example 1

[0041] A method for encapsulating liquid metal microspheres comprises the following steps:

[0042] Step 1: Prepare hydrogel powder with self-gelling properties and adhesion.

[0043] ① Preparation of p(AAc-co-TMSPMA) hydrogel:

[0044] Slowly pour 160mL of deionized water, 80mL of acrylic acid, 2.1mL of 0.1mol / L N,N-methylenebisacrylamide, 60uL of 1mol / L α-ketoglutaric acid and 120uL of [3-(methacryloyloxy)propyl]trimethoxysilane [TMSPMA] into a 500mL glass. Subsequently, the precursor solution was fully mixed and bubbles were removed under mechanical stirring and water bath ultrasound. Then, a 50mL syringe was used to load the precursor solution and ultrasound was used to remove visible bubbles inside. Finally, these syringes filled with hydrogel prepolymer solution were divided into plastic sealing bags and filled with N 2 Protect and place in a 365nm UV curing box for about 3 to 5 hours.

[0045] ②p(AAc-co-TMSPMA) hydrogel dialysis:

[0046] The solidified hydrogel is taken out from the needle tube and soaked in 1000 mL of deionized water. The dialysate is replaced every 24 hours. The unpolymerized acrylic acid monomers and other small molecules in the hydrogel can be removed by replacing the dialysate about 3 to 5 times.

[0047] ③ Preparation of p(AAc-co-TMSPMA) gel dry powder:

[0048] The hydrogel after dialysis is placed in liquid nitrogen. When the liquid nitrogen is no longer boiling, it is taken out of the liquid nitrogen and placed in a mixing crusher to be crushed to obtain white hydrogel powder. Subsequently, the powder is placed in a freeze dryer and freeze-dried at about minus 70°C. The powder is taken out after about 48 hours to obtain the target gel dry powder. Finally, the powder is passed through a powder sifter (100 mesh to 400 mesh) to obtain a gel dry powder with uniform particle size distribution, and placed in a drying cabinet for use.

[0049] Step 2: Prepare solidified spherical liquid metal.

[0050] Gallium-based or bismuth-based metals or alloys (preferably pure gallium, gallium-indium alloy, bismuth-indium-tin alloy, bismuth-indium alloy or gallium-indium-tin alloy) are accurately filled into the spherical silicone mold by a pipette. In order to allow the liquid metal to be completely filled into the container environment, the mold can be gently dropped several times so that the liquid metal is completely in contact with the silicone mold to reduce the surface defects of the solidified liquid metal ball. Finally, the mold filled with liquid metal is placed in an ultra-low temperature refrigerator (-80°C), and the solidified spherical liquid metal can be taken out after about 1 hour.

[0051] Step 3: Encapsulate the spherical liquid metal.

[0052] ① In order to prevent the gel dry powder from absorbing moisture in the environment and melting the liquid metal, the ambient humidity needs to be controlled below 40% and the temperature needs to be controlled below the melting point of the liquid metal before subsequent experimental preparation can be carried out.

[0053] ②First, take the same volume of p(AAc-co-TMSPMA) gel powder as the solidified liquid metal ball and place it in a plastic container. Then use a spray bottle to spray the atomized glycerol aqueous solution (V 甘油 :V 水 =1:4) sprayed on the liquid metal ball and put into a container covered with dry powder, shaking the container to make the metal ball inside roll. After rolling for about 5 seconds, the metal ball with dry powder attached can be taken out. Then put it into a new plastic container and continue to roll for about 10 seconds to remove the pseudo-adherent dry powder on the surface. This is conducive to improving the thickness uniformity of the subsequent hydrogel shell layer. Finally, use a spray bottle to spray the glycerol aqueous solution on the metal ball to promote the re-dissolution of the gel dry powder attached to the surface to form a complete hydrogel film.

[0054] ③ In order to obtain liquid metal hydrogel capsules of different thicknesses, the small balls can be placed in a container covered with dry powder and the steps in ② can be repeated to obtain hydrogel capsules with controllable shell thickness.

[0055] Figure 2 This is a morphological photograph of the liquid metal hydrogel capsule prepared in Example 1. It can be seen from the figure that the surface of the liquid metal is completely covered by the hydrogel coating, and the coating can still maintain the wrapped state and appear transparent after swelling.

[0056] The method for measuring the amount of powder on the surface of the liquid metal ball is as follows: measure the original mass m of the liquid metal ball and 0 , total mass after water spraying m 1 , total mass after powder coating m 2 , the total mass after the final water spraying m 3 , and then the total mass after powder coating m 2 Total mass after deducting the water spray m 1 It is the mass of powder used for roller coating.

[0057] The method for measuring the shell thickness on the surface of the liquid metal ball is as follows: use a vernier caliper to measure the diameters of three liquid metal hydrogel balls with the same number of rolling coatings, subtract the diameter of the original liquid metal ball, divide it by 2, and take the average value to obtain the shell thickness on the surface of the liquid metal ball under different rolling coating times.

[0058] Figure 3 a) is the amount of powder on the surface of the liquid metal ball under different rolling times; b) is the thickness of the shell layer on the surface of the liquid metal ball under different rolling times. Figure 3 It can be seen that the powder required for each roll coating is about 16 mg, and as the number of roll coatings increases, the thickness of the surface coating will also increase. The thickness increased by each roll coating layer is also similar, about 120 um.

[0059] The method for determining the compression performance of the liquid metal hydrogel capsule is to place the liquid metal hydrogel ball under an Instron tensile machine for testing, set the accessories and software to compression mode, and then perform a compression test with a compression speed of 10 mm / min. The force-working distance curve is obtained and converted into a force-strain curve.

[0060] Figure 4 The compression performance of liquid metal hydrogel capsules with different shell thicknesses. Figure 4 It can be seen that liquid metal can resist a certain compression after being coated with a hydrogel coating, and as the coating becomes thicker, the pressure it can withstand increases accordingly. These liquid metal hydrogel capsules only rupture when they achieve a strain of about 80%.

[0061] Example 2

[0062] The difference from Example 1 is that acrylic acid is replaced by 2-butenoic acid. The obtained liquid metal hydrogel capsule is as follows Figure 5 shown.

[0063] Example 3

[0064] The difference from Example 1 is that [3-(methacryloyloxy)propyl]trimethoxysilane is replaced by vinyltrimethylsilane. The obtained liquid metal hydrogel capsule is as follows Figure 6 shown.

[0065] Comparative Example 1

[0066] A method for encapsulating liquid metal microspheres comprises the following steps:

[0067] Step 1: prepare hydrogel prepolymer solution.

[0068] Slowly pour deionized water, acrylic acid, 1 mol / L α-ketoglutaric acid and [3-(methacryloyloxy)propyl]trimethoxysilane into a 500 mL glass cup. Then, the precursor solution is fully mixed and bubbles are removed under mechanical stirring and water bath ultrasound. Finally, the treated prepolymer solution is placed in a nitrogen-filled glove box for use.

[0069] Step 2: prepare solidified spherical liquid metal in the same manner as in Example 1.

[0070] Step three: encapsulate the spherical liquid metal.

[0071] In a glove box filled with nitrogen, the hydrogel prepolymer prepared in step 1 is placed in a UV curing box and cured to a semi-fluid state to increase its adhesion to the liquid metal spheres and reduce the sedimentation of the gel. The cured liquid metal spheres are then dipped into the semi-fluid hydrogel, held for about 30 seconds, and then taken out and quickly placed in a UV curing box for further final curing. At this time, in order to avoid the melting of the liquid metal under the irradiation of the ultraviolet lamp, a refrigeration device or ice cubes needs to be arranged below. After waiting for 1 hour, it is taken out to obtain a liquid metal hydrogel capsule with a thin layer of hydrogel.

[0072] Compared with Example 1, the liquid metal hydrogel capsule obtained by this method always has less gel at some contact points, and due to gravity, there is always more gel at the bottom, such as Figure 7 As shown in Figure 1, this will lead to uneven gel layer on the liquid metal ball. In addition, after the liquid metal is melted, the external gel layer is too thin and has poor mechanical properties, so it is impossible to achieve stable wrapping of the liquid metal. Figure 8 shown.

[0073] Comparative Example 2

[0074] A method for encapsulating liquid metal microspheres comprises the following steps:

[0075] Step 1: Preparation of hydrogel powder

[0076] ① Preparation of pAAc hydrogel:

[0077] Slowly pour deionized water, a large amount of acrylic acid, a small amount of N,N-methylenebisacrylamide and α-ketoglutaric acid into a 500mL glass cup. Then, the precursor solution is fully mixed and bubbles are removed under mechanical stirring and water bath ultrasound. Then, a 50mL syringe is used to load the precursor solution and ultrasound is used to remove visible bubbles inside. Finally, these syringes filled with hydrogel prepolymer solution are divided into plastic sealing bags and filled with N 2 Protect and place in a 365nm UV curing box for about 24 hours.

[0078] ② Dialysis:

[0079] The solidified hydrogel is taken out from the needle tube and soaked in 1000 mL of deionized water. The dialysate is replaced every 24 hours. The unpolymerized acrylic acid monomers and other small molecules in the hydrogel can be removed by replacing the dialysate about 3 to 5 times.

[0080] ③ Preparation of gel dry powder:

[0081] The hydrogel after dialysis is placed in liquid nitrogen. When the liquid nitrogen is no longer boiling, it is taken out of the liquid nitrogen and placed in a mixing crusher for crushing to obtain white hydrogel powder. Subsequently, the powder is placed in a freeze dryer for freeze drying. After about 48 hours, the powder is taken out to obtain the target gel dry powder. Finally, the powder is passed through a powder sifter (100 mesh to 400 mesh) to obtain a gel dry powder with uniform particle size distribution, and placed in a drying cabinet for use.

[0082] Step 2: prepare solidified spherical liquid metal in the same manner as in Example 1.

[0083] Step three, encapsulating the spherical liquid metal, the method is the same as that in Example 1.

[0084] Compared with Example 1, without the covalent cross-linking effect of [3-(methacryloyloxy)propyl]trimethoxysilane [TMSPMA], the hydrogel shell layer will experience a sharp decrease in mechanical properties during the acid or water soaking process, and even powder dispersion and failure to form. Therefore, it is not suitable for preparing stable target liquid metal hydrogel capsules. Fig. 9 The figure shows the pAAc powder after soaking in water. It can be seen from the figure that the prepared coating cannot maintain good integrity in water and the coating cracking phenomenon occurs.

[0085] Comparative Example 3

[0086] The difference from Example 1 is that [3-(methacryloyloxy)propyl]trimethoxysilane [TMSPMA] is replaced by N-isopropylacrylamide. Fig.10 As shown in A, the presence of acrylic acid can ensure that the powder forms a complete film on the metal ball after absorbing water and re-dissolving, but the loss of the polymer chain of TMSPMA copolymer cannot achieve strong adhesion on the metal ball ( Fig.10 As shown in B), and the stability and mechanical properties in aqueous solution ( Fig.10 (as shown in C in the figure).

[0087] Comparative Example 4

[0088] The difference from Example 1 is that acrylic acid is replaced by acrylamide. Fig.11As shown in A in FIG, the prepared p(AAm-co-TMSPMA) powder cannot be re-dissolved into a gel after adding a glycerol aqueous solution without sufficient hydrogen bonding provided by a large number of carboxyl groups, and most of the powders do not adhere to each other. Fig.11 As shown in B, the presence of TMSPMA can provide a certain viscosity to coat the powder on the surface of the liquid metal sphere, but the resulting hydrogel layer is not strong in integrity and tends to appear as a wire-drawn shape rather than a complete stretched film.

[0089] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A method for encapsulating liquid metal microspheres, characterized in that: The steps include: Step 1, preparing a hydrogel powder with self-gelling properties and adhesion: mixing a polymerizable small molecule monomer A with a carboxyl group or a hydroxyl group, a polymerizable small molecule monomer B with a silanol group, a crosslinking agent, a photoinitiator, and deionized water in a volume ratio of 40-180:0.1-1:1-3:0.05-0.1:60-200, mechanically stirring and mixing, removing bubbles, and UV curing at room temperature for 3 to 5 hours; dialyzing to remove unpolymerized monomers with carboxyl groups or hydroxyl groups and other uncrosslinked chemical substances in the hydrogel; crushing, freeze-drying, and sieving to obtain a hydrogel powder with a particle size of 100 mesh to 400 mesh; Prepare solidified spherical liquid metal, first shape the liquid metal into a sphere with a particle size of 1 mm to 3 cm through a mold, and then solidify it at a temperature of 10°C to -30°C; Step 2: Encapsulate spherical liquid metal: control the ambient humidity below 40% and the temperature below the melting point of the liquid metal, spray the atomized glycerol aqueous solution on the liquid metal balls and put them into a container covered with hydrogel powder, shake the container to allow the metal balls inside to roll, and take out the liquid metal balls after the powder completely covers the liquid metal balls. Then put them into a new plastic container and continue rolling to remove the pseudo-adherent dry powder on the surface; finally, spray a small amount of glycerol aqueous solution to cover the surface of the metal balls to promote the re-dissolution of the gel dry powder attached to the surface to form a complete hydrogel film.

2. The packaging method according to claim 1, characterized in that: The polymerizable small molecule monomer A having a carboxyl group or a hydroxyl group is one or more of acrylic acid, 2-butenoic acid and polyvinyl alcohol.

3. The packaging method according to claim 1, characterized in that: The polymerizable small molecule monomer B with silanol group is one or both of [3-(methacryloyloxy)propyl]trimethoxysilane and vinyltrimethylsilane.

4. The packaging method according to claim 1, characterized in that: The cross-linking agent is one or both of N,N-methylenebisacrylamide and polyethylene glycol dimethacrylate.

5. The packaging method according to claim 1, characterized in that: The photoinitiator is one or more of benzophenone, α-ketoglutaric acid, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

6. The packaging method according to claim 1, characterized in that: The liquid metal is a gallium-based or bismuth-based metal or alloy.

7. The packaging method according to claim 1, characterized in that: The dialyzed hydrogel is placed in liquid nitrogen. When the liquid nitrogen is no longer boiling, it is taken out from the liquid nitrogen and placed in a stirring crusher for crushing to obtain white hydrogel powder. The powder is then placed in a freeze dryer for freeze drying at -70°C.

8. The liquid metal hydrogel capsule obtained by the encapsulation method according to claims 1 to 7.

9. Application of the liquid metal hydrogel capsule according to claim 8 in the fields of thermal management, interventional medicine, and soft robotics.

Citation Information

Patent Citations

  • Biocompatible hydrogel dry powder as well as preparation method and application thereof

    CN113563611A

  • Hydrogel coating for inhibiting cavitation phenomenon and preparation method thereof

    CN115558364A

  • Memory Management System and Method based on Non-Uniform Memory Access

    KR102685038B1

  • Method for producing microcapsules or beads

    US20200171454A1